2021
DOI: 10.5897/ajest2021.3064
|View full text |Cite
|
Sign up to set email alerts
|

An analytical assessment of climate change trends and their impacts on hydropower in Sondu Miriu River Basin, Kenya

Abstract: Hydropower is cost effective environment friendly and worldwide proven sustainable energy source. Driven by streamflow stream flows, it is vulnerable to climate change and land use change. The hydropower production from the two-existing run-of-river hydropower projects on the Sondu Miriu River are vulnerable to rainfall variability and requires proper understanding of the climate change trends and policies to support sustainable hydropower development and put in place strategies for building resilience for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Watershed Setup Module: The watershed setup module includes several display applications and a framework for generating watersheds [ 35 ]. This module allows users to incorporate streams, reservoirs, gauge locations, time-series locations, and hydrologic and hydraulic data specific to a particular area.…”
Section: Methodsmentioning
confidence: 99%
“…Watershed Setup Module: The watershed setup module includes several display applications and a framework for generating watersheds [ 35 ]. This module allows users to incorporate streams, reservoirs, gauge locations, time-series locations, and hydrologic and hydraulic data specific to a particular area.…”
Section: Methodsmentioning
confidence: 99%
“…Sondu River drops about 1800 m between the source areas at about 2900 m and the lake level at about 1130 m above sea level (42,46). The general land uses in the basin are agriculture, forest, rain-fed shrub crop (tea estates) mainly on the upper elevations bordering the forest, and settlements scattered across the basin (5,47,48). The area under forest comprises the forest reserve and covers about 84000 ha, which is about 20% of the total Mau Forest coverage.…”
Section: Area Of Studymentioning
confidence: 99%
“…Recently, climate change has caused the watershed to experience frequent floods, droughts, and seasonal rainfall shifts [ 22 ]. The projected impact of climate change in the Upper Awash watershed also showed that it is expected to have a greater magnitude and direction than the influence already seen over the past three decades [ [22] , [23] , [24] , [25] ].…”
Section: Introductionmentioning
confidence: 99%